2019
DOI: 10.3390/nu11122969
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Endoscopic Gastrostomy versus Nasogastric Tube Feeding: Oropharyngeal Dysphagia Increases Risk for Pneumonia Requiring Hospital Admission

Abstract: Background: Aspiration pneumonia is the most common cause of death in patients with percutaneous endoscopic gastrostomy (PEG) and nasogastric tube (NGT) feeding. This study aimed to compare PEG versus NGT feeding regarding the risk of pneumonia, according to the severity of pooling secretions in the pharyngolaryngeal region. Methods: Patients were stratified by endoscopic observation of the pooling secretions in the pharyngolaryngeal region: control group (<25% pooling secretions filling the pyriform sinus)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 38 publications
1
24
0
1
Order By: Relevance
“…Löser et al (8) reported intracerebral hemorrhage 6.2% and cerebrovascular events 12.4% in their study covering a four-year period. Chang et al (9) reported that neurological disorders were 46%, esophageal damage 39.2%, and head and neck tumors 14.4%. It is clear that these rates vary according to the characteristics of the centers where the research was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Löser et al (8) reported intracerebral hemorrhage 6.2% and cerebrovascular events 12.4% in their study covering a four-year period. Chang et al (9) reported that neurological disorders were 46%, esophageal damage 39.2%, and head and neck tumors 14.4%. It is clear that these rates vary according to the characteristics of the centers where the research was conducted.…”
Section: Discussionmentioning
confidence: 99%
“… 14 ) One of the reasons for the absence of a statistically significant difference in the rate of aspiration pneumonia between those receiving PEG and NGT was heterogeneity arising from the inclusion of patients with various diseases, such as stroke and head and neck cancer, and those in the acute and chronic phases of the disease. 14 , 15 , 16 , 17 ) In the current study, we compared the effect of PEG and NGT only in patients with stroke who were in CRWs and who had severe dysphagia. We also selected patients who continued to receive the same method of enteral feeding (PEG or NGT) during their entire stay in CRWs.…”
Section: Discussionmentioning
confidence: 99%
“…One reason for the absence of a significant difference between PEG and NGT in terms of the rate of aspiration pneumonia is the heterogeneity among the study patients who had various diseases such as stroke and head and neck cancer and were in the acute and chronic phases of disease. 14 , 15 , 16 , 17 ) As a result, it is necessary to investigate the difference in the rates of aspiration pneumonia between patients receiving PEG and NGT by focusing on a specific disease and phase (acute, convalescent, or chronic) to clarify whether PEG or NGT is the optimal enteral feeding method for stroke patients who cannot take adequate nutrition orally.…”
Section: Introductionmentioning
confidence: 99%
“… 37 As a result, secretion accumulation in the pyriform sinus or a leak into the laryngeal vestibule could result in aspiration in these patients. 38 …”
Section: Discussionmentioning
confidence: 99%